MuFBDTester: A mutation‐based test sequence generator for FBD programs implementing nuclear power plant software. (3rd May 2022) - Liu, Lingjun; Jee, Eunkyoung; Bae, Doo‐Hwan
Summary: Function block diagram (FBD) is a standard programming language for programmable logic controllers (PLCs). PLCs have been widely used to develop safety‐critical systems such as nuclear reactor protection systems. It is crucial to test FBD programs for such systems effectively. This paper presents an automated test sequence generation approach using mutation testing techniques for FBD programs and the developed tool, MuFBDTester. Given an FBD program, MuFBDTester analyses the program and generates mutated programs based on mutation operators. MuFBDTester translates the given program and mutants into the input language of a satisfiability modulo theories (SMT) solver to derive a set of test sequences. The primary objective is to find the test data that can distinguish between the results of the given program and mutants. We conducted experiments with several examples including real industrial cases to evaluate the effectiveness and efficiency of our approach. With the control of test size, the results indicated that the mutation‐based test suites were statistically more effective at revealing artificial faults than structural coverage‐based test suites. Furthermore, the mutation‐based test suites detected more reproduced faults, found in industrial programs, than structural coverage‐based test suites. Compared to structural coverage‐based test generation time, the time required by MuFBDTester to generate one test sequence from industrial programs is approximately 1.3 times longer; however, it is considered to be worth paying the price for high effectiveness. Using MuFBDTester, the manual effort of creating test suites was significantly reduced from days to minutes due to automated test generation. MuFBDTester can provide highly effective test suites for FBD engineers. Abstract : We present an automated test sequence generation approach using mutation testing techniques for FBD programs and the developed tool, MuFBDTester. MuFBDTester can provide highly effective test suites for FBD engineers.